A REVIEW OF HOW THE USE OF CHATGPT IN LEARNING AFFECTS STUDENT WELL-BEING - Սոնգ, Զեյու (Արդի հոգեբանություն, 2025)
This article provides a review of the current relations between using ChatGPT for learning and student well-being. ChatGPT is an AI-based chatbot that can be used to assist students in their learning. It can provide personalized learning recommendations, answer questions, and offer feedback on assignments. However, the impact of using ChatGPT on student well-being can vary depending on several factors.Firstly, the design and implementation of ChatGPT can affect the student's experience. If the chatbot is poorly designed or implemented, it can cause frustration or confusion, which can negatively impact the student's well-being. On the other hand, a well-designed chatbot that is easy to use and provides helpful feedback can enhance the student's learning experience and overall well-being. Secondly, the student's perception of ChatGPT can also affect their well-being. If the student views ChatGPT as a helpful tool that enhances their learning experience, it can lead to positive emotions and a sense of accomplishment. However, if the student sees ChatGPT as a replacement for human interaction or as a means of surveillance, it can lead to negative emotions such as anxiety or fear. Lastly, the role of ChatGPT in the overall learning environment can also impact student well-being. If ChatGPT is used as a supplement to traditional teaching methods and provides additional support, it can enhance the student's learning experience and improve their well-being. However, if ChatGPT is used as a replacement for human teachers or as the sole means of learning, it can lead to a sense of isolation and disconnection from the learning experience.This article analyzes the impact of using ChatGPT on student well-being depending on several factors such as design, implementation, perception, and role in the overall learning environment. When designed and implemented well, and used as a supplement to traditional teaching methods, ChatGPT can enhance the student's learning experience and improve their well-being.